Persistência de cepas de Escherichia coli genérica e de Stec não-O157 em solos agricultáveis - Correa, Taciana Pretti [UNESP] (2015)
Shiga toxin producing Escherichia coli non- O157 serogroup has been recognized as cause of serious diseases in human. However, research on the persistence of STEC non- O157 in preharvest is limited. In the current study we analysed the survival behavior of generic E.coli, E.coli carrying eae gene and STEC non- O157 strain carrying stx1, stx2 and eae gene in two agricultural soils, sugar cane culture and grassland in two different situations autoclaved soil and non- autoclaved soil. The E.coli strains were inoculated in both soils in a microcosm system which was analysed for sixty days. Results showed that all E.coli strains were recovered in a smoller number in non- autoclaved soils than in the autoclaved soils. Also was verified that the STEC non- O157 strains survived longer than the generic E.coli strain in the non autoclaved grassland soil, at least for sixty days. We should pay more attention to the STEC non- O157 serogroup long survival in grassland soil and its potential environmental risk